TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PENERAPAN TARIF JUAL BELI AIR PDAM TIRTA MEDAL KABUPATEN SUMEDANG (Studi Kasus Di Lingkungan Cipada Kelurahan Kotakulon Kecamatan Sumedang Selatan) - Luthfi S. Abdurrahman Al Ghafiqi; Ateng Rohendi (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
AbstractThe regional drinking water company (PDAM) Tirta Medal Sumedang is a company engaged in the distribution of water that sells its products, namely in the form of clean water. But in the application of the charge, are likely to be detrimental to customers. The rates applied PDAM Sumedang based on decision letter of Regent Sumedang number: 690/KEP. 51.0-HUK/2015 about the determination of the tariff adjustment of drinking water in the Area of drinking water for the water Company Medal Sumedang wear wearing 10 minimum cubic meters. This means that although customers in a month to wear the water PDAM of 5, 6, or 7 cubic meters then the payment is charged to the customer remain, namely 10 cubic meters. This research aims to find out: first, knowing and describe practice of selling water PDAM, the determination of the price classification, and the customer PDAM Tirta Medal; and second, an analysis of the economic law of Sharia against the application of the price and selling the water PDAM in the environment Cipada Kotakulon Village sub district of Sumedang Selatan Sumedang. Research methodology descriptive method used is a study that attempted to observe the problems systematically and accurately about the facts and the nature of the particular object. Descriptive research is aimed at exposing and illustrating the practice and application of fares and selling water PDAM Tirta Medal Sumedang and perspective of economic law according to Sharia law. The fare is the price list which is manifested in the form of currency. While the selling is the exchange of property between two parties on the basis of mutual consent and moving belong with the dressing that can be justified, it means the item is interchangeable with the replace tool which can be justified. The results of such research, researchers concluded: first, the practice of buying and selling of water PDAM Tirta Medal Sumedang is to manage and distribute their products (fresh water), accept the installation of connections new subscription, provide the information It takes consumers, responding to complaints from consumers, and serve the payments, while the determination of the price of the water and its customers set up based on the decision letter of the Regent of Sumedang number: 690/KEP. 51.0-HUK/2015 December 30, 2015; and second, the application of the tariff and selling water TAPS Tirta Medal Sumedang based on DECREE of the Regent of Sumedang number: 690/KEP. 51.0-HUK/2015 does not comply with the laws of the Sharia, because economic mechanism pricing in economic law of Sharia should be in accordance with the trends of al-Sharia, i.e. the realization of kemashlahatan and avoid any damage to the relationship between human (hablum min an-nas). The authors suggest the need for further regulation of the PDAM Sumedang and also local governments in implementing the water tariff. Given the community or customers who complained a lot and feel aggrieved by the rate of water PDAM.